การพัฒนารูปแบบเสริมสร้างสมรรถนะครูด้านการจัดการเรียนรู้วิทยาศาสตร์ เชิงสร้างสรรค์และผลิตภาพตามทฤษฎีสร้างสรรค์ความรู้ผ่านชิ้นงาน ร่วมกับแนวคิดการเสริมต่อความรู้: The Development of A Model for Enhancing Teachers Competency in Science Learning Management with Creativity and Productivity Based Using Constructionism Theory Together with Scaffolding Approach - notana, watcharapong; Kaewurai, Wareerat (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2023)
This research aimed to develop a model for enhancing teachers’ competency in science learning management with creativity and productivity based on using constructionism theory together with scaffolding approach. There were 4 research steps. Step 1 was studying information about teachers’ competency in science learning management with creativity and productivity. Step 2 was creating and examining the quality of the model for enhancing teachers’ competency. Step 3 was studying the results of using this model. Step 4 was evaluating the model by inputs, processes and outputs. The target group who were 18 elementary school science teachers under the Nan Primary Education Service Area Office1.The data were analyzed by using percentage, mean, standard deviation, and t-test. The findings are as follows. 1)The results of studying the competency of science learning management with creativity and productivity showed that the competency in science learning management with creativity and productivity was, overall, at a high level ( = 3.65, S.D. = 0.66). 2) The results of creating and examining the quality of the model for enhancing teachers’ competency in science learning management with creativity and productivity consisted of 1) principles, 2)goals, 3) contents, 4) development process, and 5) measurement and evaluation. The model was at a high level ( = 4.48, S.D. = 0.48) and had an effectiveness index of 53.02%. 3) The teachers had knowledge and understanding after using this model were significantly higher than before, at the .05 level. The teachers' ability to write a learning management plan of the teachers after the development was 79.37%, and manage learning activities was 82.28%, higher than the 70% standard criteria, which was statistically significant at the .05 level. Additionally, the teachers had a positive attitude towards science learning management with creativity and productivity higher than before the development, which was statistically significant at the .05 level. 4. Results of the evaluation for the model showed that the opinions towards this model were at a high level ( = 4.41, S.D. =0.62).